Efficacy of pembrolizumab in advanced cancer of the vulva: a systematic review and single-arm meta-analysis - Schwab, Roxana; Schiestl, Lina Judit; Cascant Ortolano, Lorena; Klecker, Philip Herbert; Schmidt, Mona Wanda; Almstedt, Katrin; Heimes, Anne-Sophie; Brenner, Walburgis; Stewen, Kathrin; Schmidt, Marcus; Hasenburg, Annette (Frontiers in Oncology, 2024)
Introduction Vulvar cancer carries a favourable prognosis in early stages. However, therapeutic options for advanced or recurrent cases are limited despite a variety of therapeutic modalities, such as extensive surgical resection, chemotherapy, and radiotherapy. The most important emerging treatment modalities are immune checkpoint inhibitors. This systematic review and meta-analysis aims to assess the efficacy and safety of pembrolizumab, an immune checkpoint inhibitor, in women with advanced vulvar cancer. Materials and methods Following a comprehensive search, review, and appraisal, two relevant single-arm studies were included. Meta-analysis was conducted using R4.3.0 software and RStudio 2023.03.0, presenting the overall effect size with a 95% confidence interval. Heterogeneity was assessed using I2 and the Cochrane Q χ2 statistics. Results Out of 154 studies screened for eligibility, two single-arm studies involving 119 patients receiving pembrolizumab for advanced vulvar cancer were included. The pooled objective response rate (ORR) was overall 10% (95% CI: 0.00-0.84) and 9% (95% CI: 0.00-0.89) in the PD-L1 positive subgroup. In the intention-to-treat (ITT) population, 31% (95% CI: 0.04-0.85) exhibited any clinical benefit (complete response, partial response, or stable disease). In the ITT population at six months, progression-free survival (PFS) was 19% (95% CI: 0.01-0.82), and overall survival (OS) was 48% (95% CI: 0.08-0.90). At 12 months, PFS decreased to 9% (95% CI: 0.00-0.85), and OS was 33% (95% CI: 0.04-0.85). No statistically significant heterogeneity was observed in PFS and OS analyses. Discussion and conclusion This study suggests that one-third of women with advanced or recurrent vulvar cancer may, without the influence of PD-L1 status, benefit from pembrolizumab treatment despite a decline in both PFS and OS at 12 months. These findings provide support for considering pembrolizumab in the treatment paradigm for this specific subset of cancer patients. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023391888